Dança e autismo: práticas pedagógicas em dançaterapia para a motivação das relações sociais e interpessoais de crianças autistas - SANTOS, Andrea Batista dos (2021)
The present work aims to socialize the results of a bibliographical research concerning the pedagogical practices in Dance, in order to contribute to the social and interpersonal relationships of autistic children, in which I tried to answer the following question: How can one use dance as a pedagogical practice for the promotion of social and interpersonal relationships of children with autism? This is a qualitative bibliographical research, which addresses the work of researchers / authors such as Cornelsen (2007), Cunha (2010), Figueira (2018), Fux (1983, 1988) and Padilha (2008). The results indicated that the possibilities of using dance in the education of autistic children are very promising, since the autistic child needs to be stimulated, mainly through the vision and it is in this contact that the Dance interferes in a positive way in its interaction with the other. Through the recognition of one's body and body, the autistic child comes to understand that the contact is not only due to a form of need, but also to something that brings happiness, satisfaction, emotional balance and several other synaesthetic manifestations that his autistic identity, unfortunately, would not allow him to understand without the mediation, in this case, of Dance therapy.